Aptidão física, índice de massa corporal e avaliação da coordenação motora em escolares do ensino fundamental - Arcay, Jeniffer Carminati da Silva Morales [UNESP] (2015)
The present study aimed to examine the body mass index (BMI), the motor coordination and physical fitness of children from elementary school in the city of Rio Claro. Some children have difficulties in performing simple motor actions of everyday life and are consistently behind of their typically developing peers in terms of motor coordination. Children with such motor difficulties adopt a more sedentary lifestyle, which brings the increase of body weight (fat tissue) and reduced physical fitness. Generally, the children became less active in recent decades perhaps due to the focus of the physical education classes (not for health promotion), decreased participation in other practices (sports, leisure) and the easy access to children of all ages to the technologies associated with entertainment and communication. The results of this study demonstrate the importance of these variables to monitor and intervene in child development. Although the sample was convenient, the results can reasonably reflect the physical and motor development of children in general.